1992
DOI: 10.1111/j.1447-0756.1992.tb00333.x
|View full text |Cite
|
Sign up to set email alerts
|

A Sero‐Epidemiological Study on Mother‐to‐Child Transmission of HTLV‐I in Southern Kyushu, Japan*

Abstract: In vertical transmission of HTLV‐I the duration of breast‐feeding seems to be an important risk factor. In this study, we made prospective and retrospective surveys on the rate of vertical transmission of HTLV‐I in infants and their siblings born to HTLV‐I seropositive mothers. The results obtained were as follows.  In the prospective study, 885 of the 16,283 pregnant women examined were HTLV‐I seropositive, and the seropositive rate was 5.4%. The seroconversion rates of short‐term (>7 months) and long‐term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 11 publications
0
17
0
1
Order By: Relevance
“…Since the first studies, the repartition of HTLV-1 carriers in Japan is quite uneven with prevalence rates among blood donors varying from 1% in Hokkaido to more than 6% in Kyushu and Okinawa Islands in the Southern part of the archipelago (Hinuma et al, 1982; Maeda et al, 1984; Tajima, 1990). Several studies in pregnant women also revealed such a heterogeneous situation, which origin remains to be determined, with an HTLV-1 prevalence ranging from 0.5% (in North/central Japan) to 5.8% (Southern part of the country; Oki et al, 1992; Umemoto et al, 1994; Goto et al, 1997; Maehama, 2004). In some villages or towns of highly endemic areas, HTLV-1 prevalence can reach 30–40% in adults, aged more than 50 years old (Kohakura et al, 1986; Tajima et al, 1987).…”
Section: Htlv-1 Worldwide Distribution and Prevalence Estimates By Gementioning
confidence: 99%
“…Since the first studies, the repartition of HTLV-1 carriers in Japan is quite uneven with prevalence rates among blood donors varying from 1% in Hokkaido to more than 6% in Kyushu and Okinawa Islands in the Southern part of the archipelago (Hinuma et al, 1982; Maeda et al, 1984; Tajima, 1990). Several studies in pregnant women also revealed such a heterogeneous situation, which origin remains to be determined, with an HTLV-1 prevalence ranging from 0.5% (in North/central Japan) to 5.8% (Southern part of the country; Oki et al, 1992; Umemoto et al, 1994; Goto et al, 1997; Maehama, 2004). In some villages or towns of highly endemic areas, HTLV-1 prevalence can reach 30–40% in adults, aged more than 50 years old (Kohakura et al, 1986; Tajima et al, 1987).…”
Section: Htlv-1 Worldwide Distribution and Prevalence Estimates By Gementioning
confidence: 99%
“…The patient most probably acquired the infection through prolonged breast-feeding, since his mother was seropositive and he had no history of blood transfusion. It is known that HTLV-I vertical transmission is directly proportional to the time of breastfeeding [7]. In conclusion, this is a case of ATL in a young adult with distinct clinical and histological manifestations and a prolonged survival time.…”
Section: To the Editormentioning
confidence: 65%
“…They found, the transmission rate in breastfed neonates was 41% by PCR, and none of formula feeding neonates was positive [19]. In another study conducted by Toshitaka and colleagues in Japan, 16283 pregnant women were studied, and seropositive prevalence of HTLV1 in them was 5.4%, and serum change in their infants who were breastfed for less than 7 months was 3.8% and in formula-fed infants was 5.6% [20]. Sexual transmission is a significant source for acquisition of HTLV1 in adult, and overall 15–25% of children born to infected women become infected [21].…”
Section: Discussionmentioning
confidence: 99%